The Role of Spanish Grandparents and Fathers in Childcare in Spain - Meil, Gerardo; Rogero-García, Jesús (Cuadernos de Relaciones Laborales, 2014)
During the last years, fathers have become more involved on childcare in Spain. The aim of this article is to know whether this increasing involvement of the fathers replaces the care provided by the grandparents or, on the contrary, there is a complementary relationship. We used a sample from the Survey of Parental Leaves Use in Spain, which is composed by 1,125 dual earner respondents with at least one child under 13 years old. Our results show that childcare carried out by fathers and grandparents tend to be substitutive, and not complementary. Our analysis also reveals that a significant part of the dual earner couples does not receive grandparents’ support on childcare on a daily basis. The childcare provided by the maternal grandparents does not substitute the childcare carried out by the parental grandparents, but they complement each other.